Autistic Cognition: Charting Routes to Anxiety. Issue 7 (July 2021) - Stark, Eloise; Stacey, James; Mandy, Will; Kringelbach, Morten L.; Happé, Francesca
Abstract : Autism Spectrum Conditions are typified by a divergence in cognitive style from that of the non-autistic population. Cognitive differences in autism may underlie significant strengths, but also increase vulnerability to psychopathology such as anxiety, which is a major problem for many autistic people. Many autistic people also do not respond to typical psychotherapeutic interventions, suggesting that autism-specific models and interventions are needed. We advance a theoretical model explaining how three constructs, attenuated predictions, intolerance of uncertainty, and 'black and white thinking', may interact to lead to anxiety in autism. We hope to start a dialogue surrounding how we can best address specific autistic cognitive differences that may lead to distress by developing appropriate models, measurements, and psychotherapeutic interventions. Highlights: Autism appears to be related to several cognitive differences, including attenuated predictive processing and intolerance of uncertainty. Preliminary evidence also suggests a 'black and white' thinking style. In non-autistic people, anxiety is often causally related to cognitive biases, and the aforementioned cognitive differences all have strong links to anxiety in autistic people. We therefore propose a model that accounts for how these key cognitive differences are interrelated and lead to anxiety in autism specifically and also propose testable hypotheses to guide possible future research.